Straight from the CEO : the world's top business leaders reveal ideas that every manager can use (London : Nicholas Brealey, 1998)
Globalization. Radical change. Leadership. Culture. Innovation and creativity. Customer relationship.
Keywords: Business; Management; Executives; Organization; Industrial management; Success in business; Organizational change -- Management; Chief executive officers